Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1128/jvi.01027-08
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Noncoding RNA Generated bycis-Element-Mediated Protection against 5′→3′ RNA Decay Represses both Cap-Independent and Cap-Dependent Translation

Abstract: Positive-strand RNA viruses use diverse mechanisms to regulate viral and host gene expression for ensuring their efficient proliferation or persistence in the host. We found that a small viral noncoding RNA (0.4 kb), named SR1f, accumulated in Red clover necrotic mosaic virus (RCNMV)-infected plants and protoplasts and was packaged into virions. The genome of RCNMV consists of two positive-strand RNAs, RNA1 and RNA2. SR1f was generated from the 3 untranslated region (UTR) of RNA1, which contains RNA elements e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(128 citation statements)
references
References 56 publications
7
119
2
Order By: Relevance
“…Furthermore, these studies have revealed the presence of remarkable similarities between the lncRNAs and 39 UTRs of protein-coding RNAs. Interestingly, recent global transcriptome analyses suggest that many 39 UTRs give rise to independent lncRNA transcripts, and there is at least one example of a viral lncRNA that is generated from a 39 UTR after the rest of the original proteincoding message has been degraded (Iwakawa et al 2008;Mercer et al 2011). These findings, together with the results discussed above, suggest that the different classes of cellular RNA regulatory sequences share features that may contribute to their RNA-mediated mode of regulation.…”
Section: Parallels Between Lncrnas and 39 Utrssupporting
confidence: 57%
“…Furthermore, these studies have revealed the presence of remarkable similarities between the lncRNAs and 39 UTRs of protein-coding RNAs. Interestingly, recent global transcriptome analyses suggest that many 39 UTRs give rise to independent lncRNA transcripts, and there is at least one example of a viral lncRNA that is generated from a 39 UTR after the rest of the original proteincoding message has been degraded (Iwakawa et al 2008;Mercer et al 2011). These findings, together with the results discussed above, suggest that the different classes of cellular RNA regulatory sequences share features that may contribute to their RNA-mediated mode of regulation.…”
Section: Parallels Between Lncrnas and 39 Utrssupporting
confidence: 57%
“…EtBr-stained 18S/26S rRNAs were used as loading controls for Northern blotting. SR1f is a stable degradation product derived from the 3= UTR of RNA1 (28). gation in order to assess the formation of the 80S and 48S initiation complexes.…”
Section: Resultsmentioning
confidence: 99%
“…These include the large stem-loop structures present in the ambisense RNA segments of arenaviruses (Pinschewer et al 2005) and pseudoknot/double hairpin structures of coronaviruses (Stammler et al 2011). Several positive-sense plant viruses also generate some apparent subgenomic stable decay products that may arise by a mechanism similar to the flavivirus sfRNA (Iwakawa et al 2008;Peltier et al 2012). We are currently assessing if these viruses may interact with XRN1 through mechanisms related to those we describe here for Dengue and West Nile viruses.…”
Section: Discussionmentioning
confidence: 99%